Theoretical and methodological principles of the formation of professional culture and professional image among educators by means of the acmeological approach in war conditions - Kalaur, Svitlana; Soroka, Olga (Social work and education, 2023)
The relevance of the research is determined by the need for purposeful activity in the direction of the formation of professional culture and professional image of education seekers during their studies. It was analyzed the essence of professional culture and professional image, based on the analysis of psychological and pedagogical literature. There was revealed their role in the formation of a professional specialist. There are also analyzed innovations in the process of formation of professional image and professional culture. They are caused by wartime. We attribute the main role in the formation of professional culture and professional image to the acmeological approach. Considering this, it is highlighted the potential of the acmeological approach. There are analyzed its advantages in the organization of the educational process. There are proposed innovative changes that should be introduced to improve the educational process based on the acmeological approach.